Plasma Osteopontin Level as a Diagnostic Marker of Hepatocellular Carcinoma in Patients with Radiological Evidence of Focal Hepatic Lesions. Issue 1 (January 2013) - Khalil, Ashraf; Elgedawy, Jamalat; Faramawi, Mohammed F; Elfert, Ashraf; Salama, Ibrahim; Abbass, Ahmed; Elsaid, Hala; Elsebaai, Hatem
Aims: Hepatocellular carcinoma is one of the most aggressive malignant tumors and has limited treatment options. Needle-guided biopsies have been utilized as a tool to diagnose malignant focal hepatic lesions. These techniques are discouraged because of their complications. Nowadays, alpha fetoprotein is the most widely used tumor marker for screening and diagnosis of hepatocellular carcinoma. Nevertheless, this marker has limitations. The diagnostic role of plasma osteopontin as an adjuvant or alternative marker to alpha fetoprotein to detect hepatocellular carcinoma in Egyptian patients with focal hepatic lesions was evaluated in this study. Subject and methods: Eighty participants were recruited from the Egyptian National Liver Institute and were self-assigned to three groups, namely, focal hepatic lesions (n = 40), liver cirrhosis (n = 20), and controls (n = 20). Participants' plasma osteopontin and serum alpha fetoprotein levels were determined and were compared across the three groups. Results: The discriminatory ability of plasma osteopontin for hepatocellular carcinoma was lower than that of alpha fetoprotein. Osteopontin and alpha fetoprotein were not correlated with each other. Neither the gender nor the age of the patients showed a significant association with plasma osteopontin level. Conclusion: Measuring plasma osteopontin level alone has no advantage over serum alpha fetoprotein in patients with focal hepatic lesions due to chronic liver disease.